Patient Choice for Older People in English NHS Primary Care: Theory and Practice. (4th March 2014) - Harding, Andrew J. E.; Sanders, Frances; Lara, Antonieta Medina; van Teijlingen, Edwin R.; Wood, Cate; Galpin, Di; Baron, Sue; Crowe, Sam; Sharma, Sheetal
Abstract : In the English National Health Service (NHS), patients are now expected to choose the time and place of treatment and even choose the actual treatment. However, the theory on which patient choice is based and the implementation of patient choice are controversial. There is evidence to indicate that attitudes and abilities to make choices are relatively sophisticated and not as straightforward as policy developments suggest. In addition, and surprisingly, there is little research on whether making individual choices about care is regarded as a priority by the largest NHS patient group and the single largest group for most GPs—older people. This conceptual paper examines the theory of patient choice concerning accessing and engaging with healthcare provision and reviews existing evidence on older people and patient choice in primary care.